2016 IEEE MTT-S International Microwave Symposium (IMS) 2016
DOI: 10.1109/mwsym.2016.7540334
|View full text |Cite
|
Sign up to set email alerts
|

A WiFi tracking device printed directly on textile for wearable electronics applications

Abstract: A WiFi Tracking Device Printed Directly on Textile for Wearable Electronics Applications Bauyrzhan KrykpayevWearable technology is quickly becoming commonplace in our everyday life -fitness and health monitors, smart watches, and Google Glass, just to name a few. It is very clear that in near future the wearable technology will only grow. One of the biggest wearable fields is the E-textiles. E-textiles empower clothes with new functionality by enhancing fabrics with electronics and interconnects. The main obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A reference PIFA from Texas Instruments with 3.3 dBi gain [14], widely utilised in research and industry [11], has been simulated and fabricated for benchmarking. The designs were tuned for a 25 µm thick Polyimide substrate with 12 µm copper, and a 12 µm epoxy adhesive layer.…”
Section: Antennas Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A reference PIFA from Texas Instruments with 3.3 dBi gain [14], widely utilised in research and industry [11], has been simulated and fabricated for benchmarking. The designs were tuned for a 25 µm thick Polyimide substrate with 12 µm copper, and a 12 µm epoxy adhesive layer.…”
Section: Antennas Designmentioning
confidence: 99%
“…The flexible antennas were fabricated by etching polyimide copper laminates [9], or 3D and inkjet printing of the conductor where the antenna's efficiency is adversely reduced due to the material's conductivity [10]. Only the work by Krykpayev et al and Mihajlovic et al demonstrates wireless transmitters realised on a flexible substrate [11,12]. However, the utilisation of reference antenna designs makes the nodes susceptible to detuning by human proximity [13].…”
Section: Introductionmentioning
confidence: 99%
“…True E-textiles implementation can potentially be accomplished via conductive printing since printing the circuit layout directly on textiles, can eliminate the rigidness coming from PCB substrate, as shown in our previous work [28]. This method is already widely exploited to print on different substrates including paper and plastic [29][30][31][32].…”
Section: Introductionmentioning
confidence: 97%
“…Several reviews can be found dealing with biosignal measurements in general [ 49 , 50 , 51 , 52 , 53 ], or with textile integration of single circuit boards [ 54 , 55 , 56 ], thus these topics are omitted here. This review instead gives an overview of some typical applications of single circuit boards for biosignal detection, mostly based on Arduino or Raspberry Pi, which is recently not available in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%